Obstetric violence and its influence on women's health (Research, Society and Development, 2021)
Obstetric violence was recognized in Brazil by the World Health Organization in 2014 as a public health issue, through aggressions against women during pregnancy, childbirth, puerperal and newborn. The objective is to highlight the forms of obstetric violence and the rights of pregnant women that are neglected, as well as to discuss the importance of nursing to humanized childbirth. This study is a literature review, data collection was carried out in the second half of 2021, using the following databases: Scientific Electronic Library Online (SCIELO), Latin American Caribbean Health Science Literature (LILACS) and Database in Nursing (BDENF). Eleven articles published from 2010 to 2020 were analyzed. The results show that the types of obstetric violence occur physically, psychologically and verbally, occurring with the lack of information, prohibition of the companion, expropriation of the woman's body, authoritarianism of professionals health, humiliation and disrespect for humanized childbirth and assistance to pregnant women, parturient, puerperium. There must be stricter laws and policies to combat, minimize and absolutely extinguish methods harmful to the health of women and babies.